Clinical presentation of Attenuated Psychosis Syndrome in children and adolescents: Is there an age effect?. (June 2017) - Ribolsi, Michele; Lin, Ashleigh; Wardenaar, Klaas J.; Pontillo, Maria; Mazzone, Luigi; Vicari, Stefano; Armando, Marco
Abstract: There is limited research on clinical features related to age of presentation of the Attenuated Psychosis Syndrome in children and adolescents (CAD). Based on findings in CAD with psychosis, we hypothesized that an older age at presentation of Attenuated Psychosis Syndrome would be associated with less severe symptoms and better psychosocial functioning than presentation in childhood or younger adolescence. Ninety-four CAD (age 9–18) meeting Attenuated Psychosis Syndrome criteria participated in the study. The sample was divided and compared according to the age of presentation of Attenuated Psychosis Syndrome (9–14 vs 15–18 years). The predictive value of age of Attenuated Psychosis Syndrome presentation was investigated using receiver operating characteristic (ROC)-curve calculations. The two Attenuated Psychosis Syndrome groups were homogeneous in terms of gender distribution, IQ scores and comorbid diagnoses. Older Attenuated Psychosis Syndrome patients showed better functioning and lower depressive scores. ROC curves revealed that severity of functional impairment was best predicted using an age of presentation cut-off of 14.9 years for social functioning and 15.9 years for role functioning. This study partially confirmed our hypothesis; older age at presentation of Attenuated Psychosis Syndrome was associated with less functional impairment, but age was not associated with psychotic symptoms. Highlights: APS in early compared to late adolescence have been specifically investigated. Earlier age of presentation with APS is associated with more severe presentation and worse functioning. Functioning severity could be predicted by age of presentation.